2009
DOI: 10.1007/s11095-009-9912-4
|View full text |Cite
|
Sign up to set email alerts
|

Skin Solubility Determines Maximum Transepidermal Flux for Similar Size Molecules

Abstract: A key finding is that the convex dependence of maximum flux on lipophilicity arises primarily from variations in stratum corneum solubility, and not from diffusional or partitioning barrier effects at the stratum corneum-viable epidermis interface for the more lipophilic phenols. Our data support a solute structure-skin transport model for aqueous solutions in which permeation rates depend on both partitioning and diffusivity: partitioning is related to P, and diffusivity to solute size and hydrogen bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 57 publications
2
62
0
Order By: Relevance
“…Compounds with molecular weights less than 500 Da or with a log P of approximately 1 to 4 are most likely to be absorbed through the skin. [1][2][3] Thus, most of the drugs used in transdermal therapeutic systems are designed in accordance with these physicochemical parameters. 4) Many trials have investigated methods that might enhance the skin penetration of poorly absorbed compounds.…”
mentioning
confidence: 99%
“…Compounds with molecular weights less than 500 Da or with a log P of approximately 1 to 4 are most likely to be absorbed through the skin. [1][2][3] Thus, most of the drugs used in transdermal therapeutic systems are designed in accordance with these physicochemical parameters. 4) Many trials have investigated methods that might enhance the skin penetration of poorly absorbed compounds.…”
mentioning
confidence: 99%
“…Other (multiparametric) models have incorporated additional descriptors, typically describing molecular shape, solubility, polarity, and hydrogen-bonding capacity. In addition to simple and multiple linear regression approaches, non-linear modelling has also been applied, including relatively simple approaches, such as parabolic models (e.g., Lien and Gao, 1995 99 ) and bilinear models (e.g., Zhang et al, 2009 100 ) to more complex ones, such as artificial neural networks (e.g., Fatemi and Malekzadeh, 1995 101 ). Most QSARs are published in the scientific literature, although some are implemented in freely available software, such as Episuite, or commercial tools, such as Schrodinger's QikProp.…”
Section: In Silico Methodsmentioning
confidence: 99%
“…Secondly (105), a vehicle or solute leads to increase in drug solubility in the SC. For example, a study by Kadir et al (106) suggested that addition of paraffin oil to propionic acid solutions increased the flux of either theophylline or adenosine by enhancing the flux of propionic acid into the skin and accelerating the partitioning of the solutes in the modified skin barrier. There are many agents which can enhance or retard skin penetration.…”
Section: Drug-vehicle-skin Interactionsmentioning
confidence: 99%
“…Topical administration products account for an increasingly significant percentage of solute delivery candidate compounds under clinical evaluation (106). To be useful, topical products must provide efficient delivery of actives to either the systemic circulation or to the skin, but for most substances, the uppermost layer of the skin, the stratum corneum presents a substantial barrier to their penetration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation